Schoolbag Weight and Low Back Pain: A Cross-Sectional Study among Children of Public and Private Primary Schools in Cameroon - Wiliam Richard Guessogo; André Hamadou; Edmond Ebal-Minye; Jerson Mekoulou Ndongo; William Mbang-Bian; Samuel Mbouh; Pascale Mibo'o; Maurice Père de Mpele; Temfemo Abdou; Bienvenu Bongue; Samuel Honoré Mandengue; Assomo Ndemba Peguy Brice (Shiraz University of Medical Sciences, 2023)
Background: The issue of excessively heavy schoolbags remains a public health concern in Africa. This study aimed to determine the weight of schoolbags among students in the public and private sectors of Yaoundé city, Cameroon and identify factors associated with low back pain.Methods: A cross-sectional study was conducted during the first term of the 2020/2021 academic year in French-speaking private and public primary schools in Yaoundé city, Cameroon. The study involved 2000 pupils (8.41±2.11 years), with 1000 from the public sector and 1000 from the private sector. The variables analyzed included weight, height, and schoolbag weight. A questionnaire, developed specifically for this study and based on the Standardized Nordic Body Map Questionnaire, was used to collect socio-demographic information and assess potential musculoskeletal low back pain. A diagram was included to indicate the lower back area for reporting pain. The questionnaire was administered, and each student answered it, with assistance from the investigator if needed. Descriptive and inferential statistics, as well as multiple logistic regressions, were employed for data analysis.Results: The average weight of the children and their schoolbags was 28.51±8.04 kg and 4.04±1.72 kg, respectively. Nearly 45% of the pupils were carrying a schoolbag weighing more than 15% of their body weight, and 23% reported experiencing low back pain. Schoolbag weights ranging from 10-15% of body weight were associated with a threefold higher risk (OR=2.66; 95% CI=1.65 - 4.31; P<0.0001) of developing low back pain. Pupils in the public sector had a lower risk (OR=0.28; P<0.0001) of developing low back pain.Conclusion: Children in the private sector experience low back pain more frequently. Carrying heavy schoolbags is associated with low back pain among pupils.